Real-world mobility recovery after hip fracture: secondary analyses of digital mobility outcomes from four randomized controlled trials - Engdal, Monika; Taraldsen, Kristin; Jansen, Carl-Philipp; Peter, Raphael Simon; Vereijken, Beatrix; Becker, Clemens; Helbostad, Jorunn Laegdheim; Klenk, Jochen (Age & ageing, 2024)
The main focus of rehabilitation following hip fracture is to regain mobility.To estimate the progression of real-world mobility the first year after hip fracture using digital mobility outcomes.An exploratory, prospective cohort study with pooled data from four previously conducted clinical trials.We combined data from the Trondheim Hip Fracture Trial and Eva-Hip Trial in Trondheim, Norway, and the PROFinD 1 and PROFinD 2 trials in Stuttgart and Heidelberg, Germany, resulting in a sample of 717 hip fracture patients aged ≥65 years.Each of the trials assessed mobility using body-fixed sensors (activPAL) at three time points, collectively providing observations across the entire first year post-surgery. The following 24-h DMOs were calculated: total walking duration (minutes), maximum number of steps within a walking bout, and number of sit-to-stand-to-walk transfers. Continuous 1-year progression of the median, the 25th percentile, and the 75th percentile were estimated using quantile regression models with splines.The dataset contained 5909 observation days. The median daily total walking duration increased until 36 weeks post-surgery reaching 40 min; daily maximum number of steps within a walking bout increased during the first eight weeks and then stabilized at less than 100 steps; daily sit-to-stand-to-walk transfers reached a plateau after 6 weeks with less than 40 transfers.The three DMOs progressed differently and attained plateau levels at varying times during the first year after hip fracture, indicating that these Digital Mobility Outcomes provide complementary information about different aspects of mobility recovery.
Gesehen am 24.09.2025